The Implications Of Climate Change And Extreme Weather Events For Fiscal Balance And Fiscal Policy In Africa - Kunawotor, M.E.; Bokpin, G.A.; Asuming, P.O.; Amoateng, K.A. (Journal of Social and Economic Development, 2022)
African countries quite often experience weather-related events as a result of climate variability. In this study, we investigate the effects of climate change and the incidence of extreme weather events on fscal balance and the broad implications for fscal policy formulation in Africa. We employ the system GMM, fixed-efects and random-efects estimation strategies over the period 1990–2017. We find that increases in temperature change anomaly which implies a warmer climate in a meteorological year worsens fscal balance in Africa. Our fndings also reveal that weather-related events may have a signifcant impact on fscal balance, if the damage caused is large and consequential. Furthermore, African countries with relatively strong institutions and adaptive capacities tend to modulate the impact of temperature change anomaly and extreme weather events on fscal balance. We forecast that the frequent incidence of climatic disruptions and extreme weather events which are considered as external shocks may toughen the fscal consolidation eforts and debt sustainability measures of some African governments.
Research Article
Keywords: Climate change; Fiscal balance; Africa